HUBUNGAN ANTARA SELF CONFIDENCE DENGAN HASIL BELAJAR MATEMATIKA SISWA KELAS V SD NEGERI 136 PEKANBARU - Nurul Mawaddah; Syahrilfuddin Syahrilfuddin; Eddy Noviana (Tunjuk Ajar: Jurnal Penelitian Ilmu Pendidikan, 2020)
This study aims to determine whether there is significant relationship between self confidence and mathematics learning outcomes of fifth grade students at SD Negeri 136 Pekanbaru. It is a correlation research where population of all students of fifth grade at SD Negeri 136 Pekanbaru consisted of 109 students while the sampling method is cluster sampling. The instruments used are self confidence questionnaire and documentation of student mathematics learning outcomes that have been tested for validity and reliability. The data analysis used by the writer is product moment correlation test. The result shows that there is a significant relationship between self confidence and mathematics learning outcomes of fifth grade students at SD Negeri 136 Pekanbaru with a large relationship of 0.345 and it is categorized in low relationship category. This means that the increase in variable x will be followed by an increase in variable y. The coefficient of determination in this study is 0.119 which means that self-confidence contributes to student mathematics learning outcomes by 11.9% and the remaining 88.1% is caused by other factors such as teachers, infrastructure, intelligence and student motivation. The results of this study can provide information about one of the factors that affect student learning outcomes in mathematics so that the school, teachers and parents can determine effective steps to improve student mathematics learning outcomes.